Does a Depression Management Program Decrease Mortality in Older Adults with Specific Medical Conditions in Primary Care? An Exploratory Analysis. Issue 1 (19th January 2016) - Bogner, Hillary R.; Joo, Jin H.; Hwang, Seungyoung; Morales, Knashawn H.; Bruce, Martha L.; Reynolds, Charles F.; Gallo, Joseph J.
Abstract : Objectives: To determine whether treating depression decreases mortality from various chronic medical conditions. Design: Long‐term follow‐up of multisite‐practice randomized controlled trial (Prevention of Suicide in Primary Care Elderly: Collaborative Trial). Setting: Twenty primary care practices randomized to intervention or usual care. Participants: Individuals aged 60 and older identified through depression screening of random patients (N = 1, 226). Intervention: For 2 years, a depression care manager worked with primary care physicians in intervention practices to provide algorithm‐based care for depression. Measurements: Mortality risk based on a median follow‐up of 98 months (range 0.8–116.4 months) through 2008; chronic medical conditions ascertained through self‐report. Results: For heart disease, persons with major depression were at greater risk of death, whether in usual‐care or intervention practices. Older adults with major depression and diabetes mellitus in practices randomized to the intervention condition (hazard ratio = 0.47, 95% confidence interval = 0.24–0.91) were less likely to die. For other medical conditions, the point estimates for risk of death in persons with major depression were all in the direction of indicating lower risk in intervention practices but did not reach statistical significance. Conclusion: Older adults with depression and medical comorbidity pose a significant clinical and public health challenge. Evidence was found of a statistically significant intervention effect on mortality for diabetes mellitus in persons with major depression.